The Touro 12-Step: A Systematic Guide to Optimizing Survey Research with Online Discussion Boards - Ip, Eric J; Barnett, Mitchell J; Tenerowicz, Michael J; Perry, Paul J (JMIR Publications, 2010)
The Internet, in particular discussion boards, can provide a unique opportunity for recruiting participants in online research surveys. Despite its outreach potential, there are significant barriers which can limit its success. Trust, participation, and visibility issues can all hinder the recruitment process; the Touro 12-Step was developed to address these potential hurdles. By following this step-by-step approach, researchers will be able to minimize these pitfalls and maximize their recruitment potential via online discussion boards.